Advances in quadrupole and time‐of‐flight mass spectrometry for peptide MRM based translational research analysis. Issue 15 (28th July 2016) - Mbasu, Richard J.; Heaney, Liam M.; Molloy, Billy J.; Hughes, Chris J.; Ng, Leong L.; Vissers, Johannes P. C.; Langridge, James I.; Jones, Donald J. L.
Abstract : The application of unit resolution tandem quadrupole and high‐resolution orthogonal acceleration ToF mass spectrometers for the quantitation and translational analysis of proteolytic peptides is described. The MS platforms were contrasted in terms of sensitivity and linear response. Moreover, the selectivity of the platforms was investigated and the effect on quantitative precision studied. Chromatographic LC conditions, including gradient length and configuration, were investigated with respect to speed/throughput, while minimizing isobaric interferences, thereby providing information with regard to practical sample cohort size limitations of LC‐MS for large cohort experiments. In addition to these fundamental analytical performance metrics, precision and linear dynamic ranges were also studied. An LC‐MS configuration that encompasses the best combination of throughput and analytical accuracy for translational studies was chosen, despite the MS platforms giving similar quantitative performance, and instances were identified where alternative combinations were found to be beneficial. This configuration was utilized to demonstrate that proteolytically digested nondepleted samples from heart failure patients could be classified with good discriminative power using a subset of proteins previously suggested as candidate biomarkers for cardiovascular diseases.